PEMBERDAYAAN PEMUDA DUSUN KEMPUL MELALUI PEMBUATAN MEDIA DAKWAH DIGITAL BERBASIS EDUKASI ISLAM - Nurhaeda, Eva; Saryadi (khidmatan, 2025)
This community service activity aims to describe the process and impact of youth empowerment in Kempul Hamlet through the transformation of roles from consumers to producers of digital da'wah content. The main problem faced is the low participation of youth in conventional religious activities and the use of technology limited to passive entertainment. This study uses the ABCD (Asset-Based Community Development) method to optimize the potential of gadgets and youth creativity. The empowerment process focuses on producing digital da'wah infographic content using the Canva application and short Islamic educational videos for the Instagram platform. Data collection techniques included participatory observation, in-depth interviews, and documentation of created works. The results indicated a significant increase in digital literacy and religiosity among the youth, marked by the formation of the "Kempul Berdakwah" community account as a venue for routine proselytizing. This initiative proves that choosing Instagram as a platform and using popular design tools can effectively turn social media into a medium for Islamic education while building the spiritual identity of the younger generation in rural areas.